Efficacy of stapler versus hand-sewn closure after distal pancreatectomy (DISPACT): a randomised, controlled multicentre trial - Diener, Markus K.; Seiler, Christoph; Rossion, Inga; Kleeff, Jörg; Glanemann, Matthias; Butturini, Giovanni; Tomazic, Ales; Bruns, Christiane J; Busch, Olivier RC; Farkas, Stefan; Belyaev, Orlin; Neoptolemos, John P; et al. (The lancet, 2011)
Background - The ideal closure technique of the pancreas after distal pancreatectomy is unknown. We postulated that standardised closure with a stapler device would prevent pancreatic fistula more effectively than would a hand-sewn closure of the remnant. - Methods - This multicentre, randomised, controlled, parallel group-sequential superiority trial was done in 21 European hospitals. Patients with diseases of the pancreatic body and tail undergoing distal pancreatectomy were eligible and were randomly assigned by central randomisation before operation to either stapler or hand-sewn closure of the pancreatic remnant. Surgical performance was assessed with intraoperative photo documentation. The primary endpoint was the combination of pancreatic fistula and death until postoperative day 7. Patients and outcome assessors were masked to group assignment. Interim and final analysis were by intention to treat in all patients in whom a left resection was done. This trial is registered, ISRCTN18452029. - Findings - Between Nov 16, 2006, and July 3, 2009, 450 patients were randomly assigned to treatment groups (221 stapler; 229 hand-sewn closure), of whom 352 patients (177 stapler, 175 hand-sewn closure) were analysed. Pancreatic fistula rate or mortality did not differ between stapler (56 [32%] of 177) and hand-sewn closure (49 [28%] of 175; OR 0·84, 95% CI 0·53-1·33; p=0·56). One patient died within the first 7 days after surgery in the hand-sewn group; no deaths occurred in the stapler group. Serious adverse events did not differ between groups. - Interpretation - Stapler closure did not reduce the rate of pancreatic fistula compared with hand-sewn closure for distal pancreatectomy. New strategies, including innovative surgical techniques, need to be identified to reduce this adverse outcome. - Funding - German Federal Ministry of Education and Research.
Gesehen am 30.05.2022